Orbital cerebrospinal fluid space in glaucoma: the Beijing intracranial and iIntraocular pressure (iCOP) study - Wang, Ningli; Jonas, Jost B.; Weinreb, Robert N. (Ophthalmology, 2012)
Objective - Low cerebrospinal fluid pressure (CSF-P) may be involved in the pathogenesis of glaucoma. We measured the optic nerve subarachnoid space width (ONSASW) as a surrogate for orbital CSF-P in patients with primary open-angle glaucoma (POAG) with normal and high pressure and a control group. - Design - Prospective observational study. - Participants - The study included 39 patients with POAG; 21 patients had normal pressure (intraocular pressure [IOP] 21 mmHg), and 18 patients had high pressure (IOP >21 mmHg); 21 subjects formed the control group. - Methods - By using magnetic resonance imaging (MRI) with fat-suppressed fast recovery fast spin echo (FRFSE) T2-weighted sequence, we determined the ONSASW at 3, 9, and 15 mm posterior to the globe. - Main Outcome Measures - The ONSASW and optic nerve diameter. - Results - At all 3 measurement locations of 3, 9, and 15 mm, the ONSASW was significantly (P<0.001, P<0.001, and P = 0.003, respectively) narrower in the normal-pressure group (0.67±0.16, 0.55±0.09, and 0.51±0.12 mm, respectively) than in the high-pressure group (0.93±0.21, 0.70±0.12, and 0.62±0.11 mm, respectively) or the control group (0.87±0.15, 0.67±0.07, and 0.61±0.07 mm, respectively). The high-pressure and control groups did not vary significantly at 3, 9, and 15 mm (P = 0.31, P = 0.39, and P = 0.44, respectively). At all 3 measurement locations, ONSASW was narrower in the normal-pressure group compared with the high-pressure and control groups after adjustment for optic nerve diameter (P<0.01). Correspondingly, the width of the optic nerve subarachnoid space measured at 3, 9, and 15 mm behind the globe, respectively, was significantly (all P<0.05) associated with IOP after adjustment for optic nerve diameter and visual field defect. - Conclusions - The narrower orbital optic nerve subarachnoid space in patients with POAG with normal pressure compared with high pressure suggests a lower orbital CSF-P in patients with POAG with normal pressure. - Financial Disclosure(s) - The author(s) have no proprietary or commercial interest in any materials discussed in this article.